1985
DOI: 10.1073/pnas.82.7.2049
|View full text |Cite
|
Sign up to set email alerts
|

Rat Sertoli cells acquire a beta-adrenergic response during primary culture.

Abstract: Two-dimensional polyacrylamide gel electrophoresis and the radioligand (-)- [25I]iodopindolol have been used to study isoproterenol-dependent protein phosphorylation and /3-adrenergic receptor availability, respective-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

1987
1987
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…Such an acquisition of the response to ß-adrenergic agonist has been reported for different cell types such as hepatocytes (Nakamura et al, 1983), granulosa cells (Kliachko & Zor, 1981) and Sertoli cells (Kierszenbaum et al, 1985). As shown in the current study, ß-agonists did not affect or only slightly increased testosterone production in fresh interstitial cells derived from adult testis (Cooke et al, 1982;Moger et al, 1982).…”
Section: Discussionsupporting
confidence: 85%
“…Such an acquisition of the response to ß-adrenergic agonist has been reported for different cell types such as hepatocytes (Nakamura et al, 1983), granulosa cells (Kliachko & Zor, 1981) and Sertoli cells (Kierszenbaum et al, 1985). As shown in the current study, ß-agonists did not affect or only slightly increased testosterone production in fresh interstitial cells derived from adult testis (Cooke et al, 1982;Moger et al, 1982).…”
Section: Discussionsupporting
confidence: 85%
“…Under physiological conditions, most vimentin in cells is present in intermediate filaments (Klymkowsky et al, 1989;Darnell et al, 1990). In most cultured and well-spread cells, including rat Sertoli cells, vimentin IFs are shown to be a delicate network of thread-like filaments surrounding the nuclei and extending through the cytoplasm to the plasma membrane (Spruill et al, 1983; Kierszenbaum et al, 1985;Alberts et al, 1989). In the present in vivo study, vimentin in rat Sertoli cells was also shown to be concentrated around the nucleus, extending well into the cytoplasm and connecting to many specialized structures on the cell membrane.…”
Section: Distribution Of Ifs In Rat Sertoli Cellsmentioning
confidence: 99%
“…Leydig cells have beta-adrenergic receptors and catecholamines stimulate adenylate cyclase and steroidogenesis in cultured Leydig cells (Cooke et al -1982;Moger et al -1982, Damber andSelstam -1983). Beta adrenergic receptors are also present on Sertoli cells in culture and isoproterenol mimics several of the effects of FSH on cultured Sertoli cells (Verhoven et al -1979;Heindel et al -1981), whereas, in vivo the tubules probably do not contain beta adrenoreceptors (Kierszenbaum et al -1985).…”
Section: Introductionmentioning
confidence: 99%